2017
DOI: 10.1016/j.ab.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Beta-hairpin hydrogels as scaffolds for high-throughput drug discovery in three-dimensional cell culture

Abstract: Automated cell-based high-throughput screening (HTS) is a powerful tool in drug discovery, and it is increasingly being recognized that three-dimensional (3D) models, which more closely mimic in vivo-like conditions, are desirable screening platforms. One limitation hampering the development of 3D HTS is the lack of suitable 3D culture scaffolds that can readily be incorporated into existing HTS infrastructure. We now show that β-hairpin peptide hydrogels can serve as a 3D cell culture platform that is compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 40 publications
2
31
0
2
Order By: Relevance
“…Collagen and Matrigel are available in liquid form and require handling at cold temperatures to avoid premature gelation. The need for handling these hydrogels at low temperatures makes them unsuitable for common liquid handling equipment used for high-throughput screens in drug discovery (Ryan et al, 2016 ; Worthington et al, 2017 ). Fibrin is obtained through polymerization of fibrinogen, a plasma protein, and is a natural polymer formed during wound coagulation.…”
Section: The Extracellular Matrix (Ecm) and Other Microenvironmentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen and Matrigel are available in liquid form and require handling at cold temperatures to avoid premature gelation. The need for handling these hydrogels at low temperatures makes them unsuitable for common liquid handling equipment used for high-throughput screens in drug discovery (Ryan et al, 2016 ; Worthington et al, 2017 ). Fibrin is obtained through polymerization of fibrinogen, a plasma protein, and is a natural polymer formed during wound coagulation.…”
Section: The Extracellular Matrix (Ecm) and Other Microenvironmentalmentioning
confidence: 99%
“…Current peptide hydrogels that are most successfully used for 3D culture (reviewed in Worthington et al, 2015 ) are: the yeast-derived peptides EAK16 and RADA16 (Zhang et al, 1992 , 2005 ); the peptides Fmoc-FF (Fluorenylmethoxycarbonyl-diphenylalanine) and Fmoc-RGD (Fluorenylmethoxycarbonyl arginine–glycine–aspartic acid) (Jayawarna et al, 2006 ; Mahler et al, 2006 ; Smith et al, 2008 ; Orbach et al, 2009 ; Zhou et al, 2009 ); the peptide hydrogel h9e that is based on the fusion of functional domains from a silk protein and a human calcium channel (Huang and Sun, 2010 ; Huang et al, 2011 , 2013 ); FEFK and FEFKEFK, which form hydrogels in the presence of a metalloprotease (Toledano et al, 2006 ; Guilbaud et al, 2010 ); and the MAX1 peptide that gelates under physiological conditions, and like h9e, has shear-thinning properties (Schneider et al, 2002 ; Haines-Butterick et al, 2007 ). A single acid substitution derivative of the MAX1 peptide, MAX8 (Haines-Butterick et al, 2007 ), with reduced gelation times has recently been reported to be compatible with liquid handling equipment making it suitable for high-throughput drug discovery (Worthington et al, 2017 ).…”
Section: The Extracellular Matrix (Ecm) and Other Microenvironmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used natural polymers for culture are collagen and Matrigel. Other common natural polymers are silk, chitosan,, alginate, and more recently peptide hydrogels . Common semisynthetic polymers used include hyaluronic‐acid‐based hydrogels and gelatin methylmethacrylate‐based hydrogels .…”
Section: Current Progress In Modeling Cancer Biology In Vitromentioning
confidence: 99%
“…Их изобретениегидрогель на основе самоорганизующегося пептида MAX8, который в физиологических условиях образует в воде сеть с порами необходимой величины для выращивания клеточной культуры. Эксперименты были поставлены с использованием культуры клеток человеческой медуллобластомы -опухоли, возникающей в мозжечке в детском возрасте [20]. Однако эти работы выявили основной недостаток использования гидрогелей, который заключается в появлении некротических участков, формирующихся в результате затруднённого оттока отходов жизнедеятельности клеток, а также ограниченного доступа питательных сред.…”
Section: Introductionunclassified